The Provision of Tele-Counseling in Malaysia: An In-Depth Qualitative Analysis - Hafizah Mejah; Abu Yazid Abu Bakar; Salleh Amat (Bisma The Journal of Counseling, 2020)
Online counseling refers to the provision of therapeutic helping services which manipulated the electronic communication technology between a professional counselor with his or her clients via devices such as telephone, e-mail, and other social media platforms. One of the services that is getting more attention right now in Malaysia is the tele-counseling which refers to the provision of counseling service via telephone. However, since the policy on its’ provision is still inexistence, this new trend of providing counseling service is still not being accepted by the conventional practitioners, who are still believed in the face-to-face communication in order to establish an effective counseling relationship.  The objective of this concept paper is to explore views of local counseling experts on the feasibility of tele-counseling provision. The thematic analysis from research data revealed three main themes namely, (i) acceptence towards tele-counseling; (ii) advantages of tele-counseling; and (iii) limitations of tele-counseling. The result of this initial study pointed out that tele-counseling can be considered as an alternative provision for the future.   However, in Malaysia, more guiding policies and directives need to be developed so that the delivery of this services in the future will not violate the ethics of the profession which in turn will jeopardize the professionalism of the field.